Current Advances and Challenges in CAR-T Therapy for Hematological and Solid Tumors - Zhang G; Bai M; Du H; Yuan Y; Wang Y; Fan W; Zhu H; Wu D; He P; Xue B (ImmunoTargets and Therapy)
Gengtian Zhang,1,* Mengyao Bai,1,* Hanzhi Du,2 Yue Yuan,2 Yidan Wang,2 Weijing Fan,3 Huachao Zhu,2 Di Wu,2 Pengcheng He,2 Busheng Xue2 1Health Science Center, Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China; 2Department of Hematology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China; 3Department of Radiation Oncology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, 710061, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengcheng He, Department of Hematology, The First Affiliated Hospital of Xi’an Jiaotong University, No. 277, Yanta District, Xi’an, 710061, People’s Republic of China, Email hepecheng@xjtu.edu.cn Busheng Xue, Department of Hematology, The First Affiliated Hospital of Xi’an Jiaotong University, No. 277, Yanta District, Xi’an, 710061, People’s Republic of China, Email bushengxue@xjtufh.edu.cnIntroduction: Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of refractory hematological malignancies, yet significant challenges persist in extending its success to solid tumors. This review aims to provide a comprehensive overview of the current landscape and future perspectives of CAR-T therapy in both hematological malignancies and solid tumors.Methods: A thorough literature search was conducted to identify relevant preclinical and clinical studies, as well as review articles, focusing on CAR-T therapy in various hematological malignancies and solid tumors. The collected information was synthesized to discuss the current applications, challenges, and strategies for improving CAR-T therapy in these settings.Results: CAR-T therapy has demonstrated impressive clinical outcomes in treating certain hematological malignancies, such as B-cell lymphoma, leukemia, and multiple myeloma. However, the efficacy of CAR-T cells in solid tumors has been limited due to various obstacles, including tumor heterogeneity, immunosuppressive microenvironment, and off-tumor toxicities. Strategies to overcome these challenges involve advanced CAR designs, combination therapies, and novel approaches to CAR-T cell manufacturing and engineering.Conclusion: While CAR-T therapy has revolutionized the treatment of some hematological malignancies, significant hurdles remain in extending its success to solid tumors. Continued research efforts focusing on improving CAR-T cell efficacy, safety, and accessibility will be crucial in unlocking the full potential of this innovative immunotherapeutic approach across a broad spectrum of cancer types.Keywords: CAR-T, hematological malignancies, solid tumors, translational advances, clinical challenges